World Economic Outlook, October 1987. (World Economic Outlook; World Economic Outlook ;, 1987)
This paper highlights that the first half of 1987 was characterized by considerable uncertainty about the world economic situation and prospects. Following a disappointing growth performance in industrial countries in 1986, and deterioration in the external financial position of many developing countries, signs of sluggishness in some indicators early in 1987 have given rise to concern that economic activity might weaken further in 1987 and next year. Such fears have been aggravated by the persistence of historically large imbalances on current account and increasing trade frictions.